PENINGKATAN KETERAMPILAN MENULIS MENGGUNAKAN MODEL PEMBELAJARAN TALKING STICK DENGAN MEDIA ORIGAMI PADA PESERTA DIDIK KELAS IVB SDN KANDANGAN 1/121 SURABAYA - Lidya Agustina; Wahyuni Suryaningtyas; Imraatur Rafi'ah Rochani Triastuti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study has the purpose of raising skill writing class students IVB SDN Kandangan 1 Surabaya through the application of learning model talking stick in coupled with origami media questions. The research is PTK (Class Action Research) conducted in two cycle with a quantitative approach.The subject of this research is 28 students IVB class. Data collection is done through observation early diagnostic tests, writing skills tests, and judgment in attitude on liveliness students. Research shows that there has been a significant increase in students writing skills after enactment of the kind of classroom talking stick by the origami. In the cycle I, the percentage exclusion of learning reached 35%, while in cycle II is 87,5 % increased to. The enhancement of the study results, participation and motivation of students also show positive developments. For that reason, the kind of classroom talking stick by the origami proven effective in improved the skills writing students indonesian language in class 1 IVB SDN Kandangan 1/121 Surabaya.